Best Practices in Project Risk Management - Dong, Xiaoshan (Transactions on Economics, Business and Management Research, 2024)
This thesis explores the key concepts, theoretical frameworks, best practices and future trends in project risk management. Firstly, the definition and classification of risk and the basic process of project risk management are described in detail. Next, key risk management theories and models are analysed and risk management practices in different project management methodologies (e.g., waterfall model, agile methodology) are explored. The paper further discusses best practices in various stages of project risk management, including commonly used risk identification tools and techniques, qualitative and quantitative risk assessment methods, and demonstrates successful project risk management practices in different industries through case studies. Finally, the paper discusses the impact of emerging technologies on risk management and the challenges and opportunities facing project risk management in the future, and summarises the key success factors and lessons learned in project risk management. Through systematic risk management strategies, project teams can significantly improve project success rates, reduce the impact of potential problems, and drive successful project implementation.